Implementing an online peer tutoring intervention to promote reading skills of elementary students: Effects on fluency and accuracy - Sanches-Ferreira, Manuela; Martins, Helena; Valquaresma, Andreia; Alves, Sílvia (Frontiers in Education, 2022)
The global COVID-19 pandemic disrupted face-to-face teaching, having a significant impact on the teaching-learning process. As a result, many students spent less time reading (and learning to read) than they did during face-to-face instruction, requiring the use of alternative approaches of instruction. A combined online and peer tutoring intervention was designed to improve reading skills such as fluency and accuracy. Following a quasi-experimental design, this study sought to evaluated the impact of implementing an online peer tutoring intervention on the development of reading fluency and accuracy in a sample of 91 2nd and 4th graders (49.6 % female). Children were aged 6 to 10 years old (M = 7.81, SD = 1.10) and were enrolled in 5 classrooms (A, B, C, D, and E) from 3 schools in the Portuguese district of Porto, between January and May 2021. A set of 10 texts were chosen from official textbooks to assess reading fluency and accuracy. Classes were evaluated in three moments: initial (pre-intervention), intermediate (after 10 sessions) and final (post-test, after other 10 sessions). In order to examine the effects of the intervention, there was an 8-week lag between the start of the intervention in classes A, B and C (experimental group) and classes D and E (control group). Moreover, classes D and E started intervention with a gap of 5 weeks between them. Students in the experimental group registered significant higher improvements in reading accuracy and fluency than in the control group. Interaction effects revealed that students with an initial lower performance (i.e., at the frustration level) showed higher increases in reading accuracy. Furthermore, 2nd graders showed higher increases throughout the intervention while the 4th graders established their progress after the first 10 sessions of intervention. Despite the study’s limitations, the findings support the positive impact that online peer tutoring can have on promoting students’ reading skills, adding to the ongoing discussion - which has gained a special emphasis with the COVID-19 pandemic - about the development of effective strategies to promote reading abilities in the first years of school.